Accessibility and acceptability in technical manuals : a survey of style and grammatical metaphor - Lassen, Inger, 1951- (Document design companion series, 2003)
Accessibility and Acceptability in Technical Manuals is written for an audience with a general interest in readability studies, linguistics and technical writing. With the main emphasis on technical manuals the book is primarily targeted at those who have a special interest in the design and use of utility texts and how these texts are received and understood by a multifaceted audience. Accessibility is not a new research area and many explanations have been offered over the past years as to why non-experts often have difficulties in comprehending texts written by technological experts. This b.